(untitled) (INTERNATIONAL SEMINAR, 2023)
The aim of this research is to determine the application of e-government, in this case the PANDU CAKTI application at the Tulungagung Regency Population and Civil Registry Service. The research method used by researchers is qualitative research. The research design used is an analytical description research type, namely research that is used to describe in detail the research object and analyze social phenomena, in this case the application of e-government at the Population and Civil Registry Service of Tulungagung Regency. Based on the results of research conducted by the author, in implementing E Government in the Tulungagung Regency Population and Civil Registry Service, several results were produced, including that the support provided by the Tulungagung Regency Population and Civil Registry Service regarding the implementation of E-Government has been said to be very good. , in this way the support provided includes placing several services in villages far from the Tulungagung district Population and Civil Registry Office, conducting socialization about E-Government and providing facilities that support operator performance, Availability of resources to implement E-Government at the Population Service and The civil record of Tulungagung Regency, both in terms of human resources and financial resources, is quite good.